SISTEM TRANSPORTASI UMUM DI KOTA PEKANBARU TERHADAP KUALITAS HIDUP MASYARAKAT - Lanang Diayudha (Universitas Bunda Mulia, 2017)
The increasing of private vehicles and public transportation are the main cause of traffic jammed on the road. The use of public vehicles in Pekanbaru city is higher than the transportation provided by urban council through Dinas Lalu Lintas Transportasi Jalan Raya (DLLAJR). The aim of this paper is to do a research on public transportation system (oplet, ojek, city bus, taxi), also, to analyse which transportation system that have been chosen by consumer in Pekanbaru. The result shows that people are prefer to use oplet and city bus as their transportation even though it has high risk of safety and danger to them. Most people in town has their own vehicles so that the use of public transportation only for temporary period and it usually used by students who has low income. This study finally found that the ojek services are the only transportation system that can arrive to the destination in short time and it can access anywhere that cannot be accessed by other transportation system. The low cost of ojek services is the main reason that people choose it as their transportation. It is obviously shows that the use of transportation system in Pekanbaru is bused on efficiency and punctuality of the public transportation.Key WordsPublic Transportation, Efficiency, City Service